2012
DOI: 10.1002/eat.22050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating new severity dimensions in the DSM‐5 for bulimic syndromes using mixture modeling

Abstract: Objective Proposed DSM-5 severity dimensions reveal ambiguity regarding the extent to which certain features define boundaries between similar diagnoses or represent underlying dimensions within a broader category of bulimic syndromes. The current study utilized a novel mixed modeling approach that can simultaneously model latent dimensions and latent categories to address this ambiguity. Method Data from structured clinical interviews in 528 adult participants were analyzed. Results A 3-class solution wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
34
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 41 publications
10
34
2
1
Order By: Relevance
“…In particular, our results differ from Keel et al (2013) who also used the DCS approach and found evidence in favor of hybrid models. Our analyses of the “case-control” sample suggest that discrepant findings may due to the nature of the samples used.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In particular, our results differ from Keel et al (2013) who also used the DCS approach and found evidence in favor of hybrid models. Our analyses of the “case-control” sample suggest that discrepant findings may due to the nature of the samples used.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, similar to Keel et al (2013), we compared the fit of categorical, dimensional, and hybrid models to identify the best-fitting model for the nature of eating pathology. We also compared these same models in a “case-control” subset of our sample who endorsed substantial eating pathology versus no/little eating pathology.…”
mentioning
confidence: 99%
“…For instance, limited data exist regarding predictive validity of severity specifiers, and extant evidence has been inconclusive (Mustelin et al, 2016; Smink, van Hoeken, Oldehinkel, & Hoek, 2014). It is yet unclear whether the frequency of a single symptom or weight status alone are sufficient indices by which to characterize ED severity, as severity dimensions based on cognitive, affective, social, and biological domains may also yield clinically useful information (Grilo et al, 2008; Keel, Crosby, Hildebrandt, Haedt-Matt, & Gravener, 2013). It may be worth considering a multifaceted approach to characterize illness severity, and notably, the DSM-5 does not preclude the importance of other factors in determining severity (American Psychiatric Association, 2013; pp.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent factor mixture analysis of bulimic syndromes indicated a single latent severity dimension in combination with three distinct classes, but did not support clear distinctions between BN, PD, and AN-bp. Rather, the majority of PD cases were subsumed with BN and AN-bp cases in a class characterized by purging, weight phobia, and a higher level of comorbidity (Keel et al, 2013). Taken together with the present results, PD may exist along a dimension of severity within bulimic spectrum disorders characterized by loss of control eating and purging behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, comparing PD with other EDs on indicators of concurrent and predictive validity may provide empirical evidence to inform future classification systems 2 (Kendell, 1989). Moreover, there is evidence to suggest that EDs are more accurately categorized based upon both qualitative differences and the degree of underlying severity (Keel, Crosby, Hildebrandt, Haedt-Matt, & Gravener, 2013). …”
Section: Current Conceptualization For Evaluating the Validity Of Pdmentioning
confidence: 99%